Expressive suppression and enhancement during music-elicited emotions in younger and older adults - Vieillard, Sandrine; Harm, Jonathan; Bigand, Emmanuel (Frontiers in Aging Neuroscience, 2015)
When presented with emotional visual scenes, older adults have been found to be equally capable to regulate emotion expression as younger adults, corroborating the view that emotion regulation skills are maintained or even improved in later adulthood. However, the possibility that gaze direction might help achieve an emotion control goal has not been taken into account, raising the question whether the effortful processing of expressive regulation is really spared from the general age-related decline. Since it does not allow perceptual attention to be redirected away from the emotional source, music provides a useful way to address this question. In the present study, affective, behavioral, and physiological consequences of free expression of emotion, expressive suppression and expressive enhancement were measured in 31 younger and 30 older adults while they listened to positive and negative musical excerpts. The main results indicated that compared to younger adults, older adults reported experiencing less emotional intensity in response to negative music during the free expression of emotion condition. No age difference was found in the ability to amplify or reduce emotional expressions. However, an age-related decline in the ability to reduce the intensity of emotional state and an age-related increase in physiological reactivity were found when participants were instructed to suppress negative expression. Taken together, the current data support previous findings suggesting an age-related change in response to music. They also corroborate the observation that older adults are as efficient as younger adults at controlling behavioral expression. But most importantly, they suggest that when faced with auditory sources of negative emotion, older age does not always confer a better ability to regulate emotions.